2022
DOI: 10.1039/d2nj04267c
|View full text |Cite
|
Sign up to set email alerts
|

The enhanced photocatalytic properties of Bi/BiOCl composites for H2O2 production

Abstract: The development of high-efficiency economic photocatalyst for the production of hydrogen peroxide (H2O2) is of great significance for solar-to-fuel conversion. Bismuth oxychloride (BiOCl) shows giant potential for photocatalytic H2O2 production,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…The photocatalytic performance of Pt-Bi/KTa 0.5 Nb 0.5 O 3 composites was evaluated through photocatalytic N 2 -to-NH 3 conversion, by Chen et al, [197] significantly enhanced the photocatalytic performance of KTa 0.5 Nb 0.5 O 3 by using Pt-Bi alloy modification, and Wang et al [198] obtained Bi/InVO 4 photocatalysts by depositing metal Bi on indium vanadate nanosheets via a two-step hydrothermal method, which also presented an excellent photocatalytic performance in N 2 fixation. To enhance the photocatalytic generation of H 2 O 2 , Liu et al [199] synthesized Bi/BiOCl composites by in-situ chemical reduction to facilitate the separation and transport of spatial charges, Bisht et al [200] synthesized a Z-type CuO-Bi-BiOBr photocatalyst using a straightforward solution-based method, achieving high selectivity (> 99 %) and conversion (> 99 %) for the oxidation of alcohols to aldehydes or ketones. In addition, photocatalytic sterilization was investigated by Zhou et al [79] using Bi/(BiO) 2 CO 3 heterojunctions, which showed superior photocatalytic activity compared to (BiO) 2 CO 3 .…”
Section: Other Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…The photocatalytic performance of Pt-Bi/KTa 0.5 Nb 0.5 O 3 composites was evaluated through photocatalytic N 2 -to-NH 3 conversion, by Chen et al, [197] significantly enhanced the photocatalytic performance of KTa 0.5 Nb 0.5 O 3 by using Pt-Bi alloy modification, and Wang et al [198] obtained Bi/InVO 4 photocatalysts by depositing metal Bi on indium vanadate nanosheets via a two-step hydrothermal method, which also presented an excellent photocatalytic performance in N 2 fixation. To enhance the photocatalytic generation of H 2 O 2 , Liu et al [199] synthesized Bi/BiOCl composites by in-situ chemical reduction to facilitate the separation and transport of spatial charges, Bisht et al [200] synthesized a Z-type CuO-Bi-BiOBr photocatalyst using a straightforward solution-based method, achieving high selectivity (> 99 %) and conversion (> 99 %) for the oxidation of alcohols to aldehydes or ketones. In addition, photocatalytic sterilization was investigated by Zhou et al [79] using Bi/(BiO) 2 CO 3 heterojunctions, which showed superior photocatalytic activity compared to (BiO) 2 CO 3 .…”
Section: Other Applicationmentioning
confidence: 99%
“…obtained Bi/InVO 4 photocatalysts by depositing metal Bi on indium vanadate nanosheets via a two‐step hydrothermal method, which also presented an excellent photocatalytic performance in N 2 fixation. To enhance the photocatalytic generation of H 2 O 2 , Liu et al [199] . synthesized Bi/BiOCl composites by in‐situ chemical reduction to facilitate the separation and transport of spatial charges, Bisht et al [200] .…”
Section: Environmental Application Of Bi/semiconductor Photocatalystsmentioning
confidence: 99%
“…Our recent work also confirmed that Bi nanoparticle modified BiOCl boosts the spatial charge separation and transportation to enhance the photocatalytic performance for H 2 O 2 production. 37 However, to date, there has been no report about the combination of a Bi cocatalyst and oxygen vacancies to improve the photocatalytic performance of bismuth oxyhalides for photocatalytic H 2 O 2 production.…”
Section: Introductionmentioning
confidence: 99%
“…The enhancement of photocatalytic activity by noble metal loading can be mainly attributed to the following factors: (1) metal nanoparticles act as electron acceptors in photoexcited carrier transfer processes, such that the formation of Schottky barriers effectively facilitates the separation of electron-hole pairs, 26 (2) the localized surface plasmon resonance (LSPR) phenomenon of the loaded metal particles enhances the absorption of visible light in wide bandgap semiconductors (BiOCl, TiO 2 , etc. ), 27 and (3) the loading of metals can modify the surface properties of semiconductor catalysts. 28 In this work, BiOCl loaded with Pd (0.5 wt%) was successfully designed using a polyethyleneimine (PEI)-assisted method (Pd/PEI/BOC) for photocatalytic H 2 O 2 production.…”
Section: Introductionmentioning
confidence: 99%